2020
DOI: 10.1371/journal.pmed.1003062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relationship between circulating lipoprotein lipids and apolipoproteins with risk of coronary heart disease: A multivariable Mendelian randomisation analysis

Abstract: Background Circulating lipoprotein lipids cause coronary heart disease (CHD). However, the precise way in which one or more lipoprotein lipid-related entities account for this relationship remains unclear. Using genetic instruments for lipoprotein lipid traits implemented through multivariable Mendelian randomisation (MR), we sought to compare their causal roles in the aetiology of CHD. Methods and findings We conducted a genome-wide association study (GWAS) of circulating non-fasted lipoprotein lipid traits i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
504
6
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 609 publications
(544 citation statements)
references
References 72 publications
29
504
6
5
Order By: Relevance
“…25 The MR-Egger regression approach can detect and correct for directional pleiotropy albeit with compromised power. 25 Given genetic and phenotypic correlations across lipid-related traits (Pearson's R ranging from −0.49 to 0.96; Supplementary Table S3), 9 we further used multivariable inverse-variance weighted method to disentangle and compare the effects of correlated lipidtraits on ischemic stroke and subtypes. Odd ratios (ORs) and corresponding 95% confidence intervals (CIs) for outcomes were scaled to one-SD increase in levels of lipid-related traits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 The MR-Egger regression approach can detect and correct for directional pleiotropy albeit with compromised power. 25 Given genetic and phenotypic correlations across lipid-related traits (Pearson's R ranging from −0.49 to 0.96; Supplementary Table S3), 9 we further used multivariable inverse-variance weighted method to disentangle and compare the effects of correlated lipidtraits on ischemic stroke and subtypes. Odd ratios (ORs) and corresponding 95% confidence intervals (CIs) for outcomes were scaled to one-SD increase in levels of lipid-related traits.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic instruments for LDL and HDL cholesterol, triglycerides, and apoA-I and apoB were selected based on the UK Biobank study. 9 Data for the associations of the lipid-related traits associated singlenucleotide polymorphisms (SNPs) with ischemic stroke and subtypes were available from the MEGASTROKE consortium. 20 The univariable MR analysis aimed to investigate the association of individual lipid-related traits with ischemic stroke and the multivariable MR analysis aimed to compare the independent effects of correlated lipid-related traits on ischemic stroke.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the molar ratio of VLDL-TG (particle TG content) to VLDL-ApoB100 (the number of particles) is elevated in non-diabetic obese individuals with high intrahepatic TG (measured by MRS), suggesting that the secreted VLDL particles are larger and resemble the pro-atherogenic VLDL 1 [ 65 ]. Since other studies indicated that plasma ApoB concentration is a stronger predictor of CVD risk than LDL-C or plasma TG concentrations [ 67 ], further investigation is required to dissect the contribution of ApoB particle concentration vs particle content (TG or cholesterol) in determining CVD risk. It is important to bear in mind that the majority of the aforementioned studies focused on differences in intrahepatic TG and not necessarily NASH per se.…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%